Analysis of Zoning System Issues in New Student Admission to Achieve Efforts for Education Access Equalization: A Literature Review - Ardianti, Vika (Proceedings Series of Educational Studies, 2024)
Abstract The problem of equalizing access to education is one of the educational problems that is still not resolved until now. There have been many efforts made by the government related to equalizing access to education, one of which is in equalizing education in an area. One of them is in the process of admitting new students, the government implements a zoning system. The PPDB policy by implementing a zoning system is one of the policies issued by the government in the hope that it will be the right policy in overcoming equal access to education. PPDB with a zoning system is contained in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 51 of 2017 concerning Acceptance of New Learners in Kindergartens, Elementary Schools, Junior High Schools, Senior High Schools, and Vocational High Schools. This research aims to analyze the problems of the zoning system PPDB as an effort to realize efforts to equalize access to education. The approach method applied is a literature study that obtains research articles on Google Scholar. The results show that the implementation of the zoning system PPDB is in accordance with the Permendikbud but it cannot be denied that there are internal and external factors that affect the process of implementing the Zoning system PPDB policy.